Digitalisasi Sebagai Strategi Daya Saing Ekspor UMKM Indonesia - Irma Riyana; Luvita Nursyabillah Ade Meiliana; Nabillah Az Zahra; Sri Agustin (CV. SINAR HOWUHOWU, 2026)
The advancement of digital technology and global economic integration has driven business entitiesparticularly Micro, Small, and Medium Enterprises (MSMEs) to enhance their competitiveness by adopting international business strategies. This study aims to analyze the role of digital transformation in supporting the internationalization of Indonesian MSMEs, identify factors influencing successful expansion into global markets, and formulate strategies to boost MSME competitiveness in the digital trade era. The research employs a Systematic Literature Review (SLR) approach with a qualitative descriptive method, analyzing various national scholarly articles, government reports, and official documents published between 2023 and 2026. Data were analyzed using techniques involving data reduction, data presentation, and conclusion drawing to provide a comprehensive overview of MSME international business development in Indonesia. The findings indicate that digital transformation plays a crucial role in expanding access to international markets through the use of cross-border e-commerce platforms, digital marketing, electronic payments, and increasingly integrated logistics systems. Furthermore, government support manifested in MSME digitalization programs, export facilitation, and human resource capacity building strengthens the ability of MSMEs to enter global markets. However, significant challenges remain, including low digital literacy, limited access to financing, product quality that does not yet fully meet international standards, and regulatory and logistical barriers affecting export effectiveness. Therefore, synergy among the government, business players, financial institutions, educational bodies, and digital technology providers is essential to build a more inclusive and sustainable international business ecosystem. This research is expected to contribute to the development of internationalization strategies for Indonesian MSMEs and serve as a reference for experts and policymakers in formulating policies that support enhanced MSME competitiveness in the global market.